Improving health service access and wellbeing of young Aboriginal parents in an urban setting: mixed methods evaluation of an arts‐based program. (3rd September 2015) - Jersky, Michelle; Titmuss, Angela; Haswell, Melissa; Freeman, Natasha; Osborne, Perdi; Callaghan, Lola; Winters, Jennifer; Fitzpatrick, Sally; Zwi, Karen
Abstract: Objectives : To evaluate an urban art‐based community health program (Ngala Nanga Mai; We Dream) that seeks to improve health, education, empowerment and connectedness of Aboriginal parents by describing paediatric health service attendance, maternal educational engagement, participant growth and empowerment, and worker and participant experiences. Methods : Mixed methods were used. Qualitative data was collected through interviews and focus groups. Demographics, health service use and child health status were extracted from clinical records. Psycho‐social empowerment and wellbeing was measured using the Growth and Empowerment Measure (GEM). A Critical Effectiveness Factor framework that measures factors necessary for success, effectiveness and sustainability was used to assess program quality. Results : Between 2009 and 2012, 92 Aboriginal parents participated. A total of 93.5% of regular participants engaged their children at least once with paediatric health services and 27.1% undertook further education. Empowerment scores significantly improved, despite little change in psychological distress. The program operationalised all 10 Critical Effectiveness Factors for youth wellbeing. Conclusions : Ngala Nanga Mai creates an environment of social connectedness, strengthened parenting, maternal and child wellbeing and empowerment. It supports increased utilisation of health, education and support services, and early detection of treatable child health issues. Implications : Improving the health of Aboriginal children requires new strategies and learning from innovative programs. Solid baseline data, long‐term follow‐up data and meaningful health outcome data are critical to improving services and health outcomes at the program level. Ultimately, long‐term commitment to adequate resourcing is needed in order to deliver broader improvement of child health outcomes.